2017
DOI: 10.1016/j.ejphar.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 inhibitors differentially attenuate pentylenetetrazol-induced seizures and increase of pro- and anti-inflammatory cytokine levels in the cerebral cortex and hippocampus of mice

Abstract: Seizures increase prostaglandin and cytokine levels in the brain. However, it remains to be determined whether cyclooxygenase-2 (COX-2) derived metabolites play a role in seizure-induced cytokine increase in the brain and whether anticonvulsant activity is shared by all COX-2 inhibitors. In this study we investigated whether three different COX-2 inhibitors alter pentylenetetrazol (PTZ)-induced seizures and increase of interleukin-1β (IL-1β), interleukin-6 (IL-6), interferon-γ (INF-γ), tumor necrosis factor-α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 63 publications
2
16
0
Order By: Relevance
“…19,29 We hypothesize that CXB, however, carries out its effect via inhibition of pro-inflammatory cytokines, as well as inhibition of white blood cells and inflammatory cell recruitment early in the post-injury period. 30 Rabbits treated with CXB-loaded collagen membranes (group 3) did demonstrate decreased density of fibrous lesions, as well as reduced myofibroblast presence when compared to the vehicle membrane group (group 2). These data will require further investigation at earlier time points to demonstrate if this method of pharmacologic inhibition is able to decrease the density of myofibroblasts and fibrous tissue overall.…”
Section: Histopathology Datamentioning
confidence: 87%
“…19,29 We hypothesize that CXB, however, carries out its effect via inhibition of pro-inflammatory cytokines, as well as inhibition of white blood cells and inflammatory cell recruitment early in the post-injury period. 30 Rabbits treated with CXB-loaded collagen membranes (group 3) did demonstrate decreased density of fibrous lesions, as well as reduced myofibroblast presence when compared to the vehicle membrane group (group 2). These data will require further investigation at earlier time points to demonstrate if this method of pharmacologic inhibition is able to decrease the density of myofibroblasts and fibrous tissue overall.…”
Section: Histopathology Datamentioning
confidence: 87%
“…CXB is a cyclooxygenase inhibitor that selectively targets the COX‐2 enzyme, inhibiting the production of pro‐inflammatory cytokines (IL‐1β, IL‐6, IFN‐γ, TNF‐α) . This inhibition decreases the recruitment of white blood cells and other inflammatory cells and decreases sensitization in pain receptors .…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data from rodent models confirmed that enhanced activation of inflammatory pathways can contribute to enhanced excitability and lowered thresholds in the epileptic brain [3][4][5]. Moreover, increased expression rates of various pro-inflammatory mediators have been demonstrated in brain tissue from rodent epilepsy models as well as human patients with epilepsy [1,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 78%